ANALISIS TINGKAT SCHOOL WELL-BEING SISWA KELAS TINGGI DI SDN KLAMPOK 05 - Vania Hayunanda; Moh. Toharudin; Didik Tri Setiyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mapping the level of school well-being of elementary school students is still very limited, even though student well-being is an important factor that influences the comfort of learning, health, motivation, and social and emotional development of students in the school environment. This study aims to determine the level of school well-being of upper-grade students at SDN Klampok 05 and describe the condition of student well-being based on the aspects of having, loving, being, and health. The study used a descriptive quantitative approach with a survey design. The research sample consisted of 83 students in grades IV, V, and VI obtained through probability sampling techniques using the Slovin formula from a population of 104 students. Data collection was carried out using questionnaires, documentation, and interviews. The research instrument consisted of 15 statement items that have been declared valid with an r value > 0.349 and reliable with a Cronbach's Alpha value > 0.7. The results showed that the level of school well-being of students in general is in the moderate category with a percentage of 58%.